Physical activity among students during Covid-19 pandemic / Nur Hani Syazwani ... [et al.] - Syazwani, Nur Hani; Syed Mud Puad, Sharifah Maimunah; Dahlan, Nur Dalilah; Lamat, Siti Aida (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
Physical activity (PA) refers to any bodily movement produced by the contraction of skeletal muscle that requires energy expenditure above the basal level. Participating in PA is beneficial for an individual's health and wellness. It is one of the ways to maintain your well being other than practicing good dietary habits. By participating in PA, the quality of life improves. According to Centers for Disease Control and Prevention (CDC) (2019), an individual aged between 18- 64 years, needs to participate in PA at least about 150 minutes a week of moderate-intensity activities such as walking and hiking.